2015
DOI: 10.1093/treephys/tpv003
|View full text |Cite
|
Sign up to set email alerts
|

Root resistance to cavitation is accurately measured using a centrifuge technique

Abstract: Plants transport water under negative pressure and this makes their xylem vulnerable to cavitation. Among plant organs, root xylem is often highly vulnerable to cavitation due to water stress. The use of centrifuge methods to study organs, such as roots, that have long vessels are hypothesized to produce erroneous estimates of cavitation resistance due to the presence of open vessels through measured samples. The assumption that roots have long vessels may be premature since data for root vessel length are spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 57 publications
1
27
3
Order By: Relevance
“…Previous work has attributed the loss of hydraulic capacity of drought-stressed root systems to xylem embolism formation (McElrone et al, 2004;Pratt et al, 2015) and/or root shrinkage (Nobel and Cui, 1992;North and Nobel, 1997). Here, both embolism and tissue shrinkage lagged well behind lacunae formation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous work has attributed the loss of hydraulic capacity of drought-stressed root systems to xylem embolism formation (McElrone et al, 2004;Pratt et al, 2015) and/or root shrinkage (Nobel and Cui, 1992;North and Nobel, 1997). Here, both embolism and tissue shrinkage lagged well behind lacunae formation.…”
Section: Discussionmentioning
confidence: 86%
“…Dry and warm atmospheric conditions would push leaves beyond a water potential threshold and trip the hydraulic fuse in the leaf or petiole, thereby preventing both excessive water losses to the atmosphere and the buildup of hydrostatic tension in the xylem that would lead to systemic and catastrophic embolism spread (McCulloh and Woodruff, 2012;Tyree et al, 1993;Zimmermann, 1983). However, root xylem has been reported to be more vulnerable to embolism formation than shoot xylem in many woody plants (McElrone et al, 2004;Alder et al, 1996;Sperry et al, 1998;Kolb and Sperry, 1999;Ewers et al, 2000;Hacke et al, 2000;Hacke, 2000;Pratt et al, 2015). While we found that the xylem of fine roots was more susceptible to droughtinduced embolism compared to coarse roots, which agrees with previous findings (Sperry and Ikeda, 1997), our current work highlights that the weakest link in the soil-plant-atmosphere continuum is in an even more distal tissue, yet still within the plant body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as has already been shown for chaparral roots, which are also typically more hydrated than stems (Pratt et al . ), r ‐shaped curves appear to describe a relatively common hydraulic strategy that can be found in some organs, species and, now, recovery stages of woody plants.…”
Section: Discussionmentioning
confidence: 93%
“…The ratio between vessel and sample length impairs hydraulic measurements in long-vesseled species (Ennajeh et al, 2011;MartinStPaul et al, 2014;Torres-Ruiz et al, 2014;Choat et al, 2016), although this is disputed by other studies (Sperry et al, 2012;Pratt et al, 2015). Furthermore, the exponential-shaped vulnerability curves imply that a grapevine stem would be 50% embolized before its leaf and stomatal conductance decrease, which seems unlikely (Nardini and Salleo, 2000).…”
Section: Discussionmentioning
confidence: 97%